Assessing the Risk of Groundwater Contamination from Animal Waste Management - Mercurio, Frank C.; Hess, Larry G.; Robbins, Vic; Black, Richard D.; Herbel, Kevin L. (Kansas State University, 1998)
How to properly handle waste from animal production to receive benefit from the waste while preventing disease-causing organisms from entering surface and groundwater.
EP48_1998-08
Keywords: EP48; Environment and Natural Resources; Equipment and Structures; Health and Safety; EP